1982
DOI: 10.1111/j.1651-2227.1982.tb09417.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Efficiency of Phototherapy on Plasma Bilirubin Concentration

Abstract: 407 newborns with idiopathic transitory hyperbilirubinaemia were examined with regard to the decrease in serum bilirubin levels during 24 hours of intermittent phototherapy (12 hours of light exposure). The photoeffect (i.e. decrease of serum bilirubin concentration after 24 hours of therapy) showed a unique and predictable nonlinear correlation with the plasma bilirubin concentration before treatment. This relationship can be used for individualizing the duration of phototherapy and the dose of light. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
2
6
0
2
Order By: Relevance
“…A greater fall in bilirubin level has been described in association with a higher level at admission. 10,13 In agreement with such investigations, the present study showed a stronger association between decrease in bilirubin after 24 hours of therapy and bilirubin level at admission in the DP group when compared to the SP group. This finding suggests that at higher levels of bilirubin DP could be more effective than SP.…”
Section: Discussionsupporting
confidence: 80%
“…A greater fall in bilirubin level has been described in association with a higher level at admission. 10,13 In agreement with such investigations, the present study showed a stronger association between decrease in bilirubin after 24 hours of therapy and bilirubin level at admission in the DP group when compared to the SP group. This finding suggests that at higher levels of bilirubin DP could be more effective than SP.…”
Section: Discussionsupporting
confidence: 80%
“…Outra consideração diz respeito ao efeito da fototerapia ser também dependente do nível de bilirrubina no momento da internação. Uma maior queda do nível de bilirrubina foi descrita em associação a um maior nível no momento da internação 10,13 . De acordo com essas investigações, o presente estudo apresentou associação mais forte entre a redução da bilirrubina após 24 horas de terapia e os níveis de bilirrubina no momento da internação no grupo que recebeu FD quando comparado ao grupo que recebeu FS.…”
Section: Discussionunclassified
“…First, the readmission groups received significantly more irradiance to a greater surface area from underneath the baby (four BB tubes vs the Wallaby), and second, pre-phototherapy TSB levels in the readmission groups were significantly higher than the newborn groups (18.9±2.9 vs 10.7±3.1 mg/dl, P ¼ 0.000). Because the rate of TSB decline under phototherapy is directly related to the pre-phototherapy TSB level, 8 we would expect the decline to be more rapid in the readmitted infants.…”
Section: Discussionmentioning
confidence: 99%